ヒト ノ カンレイ テキオウ ニ カンスル バイオメカニクス テキ ケンキュウ ニホン ナンキョク チイキ カンソク タイ ト エスキモー ソウビ ノ ホオンセイ ウンドウセイ ノ ヒカク - 渡部, 和彦; ワタナベ, カズヒコ; 寺井, 啓; テライ, ケイ; Watanabe, Kazuhiko; Terai, Kei (1985)
P(論文) 日本南極地域観測隊(JARE)が現在使用している冬用作業装備について, 保温性および機能性を明らかにするために, グリーンランドエスキモーの装備と比較した。被検者として, 健康な男子学生4名の協力を得た。保温性のテストでは, -40℃の部屋に60分間在室させ, その間に2.5kpの負荷で15分間の自転車エルゴメーター作業を行わせ, 身体各部と装備内温をモニターした。その結果, エスキモー装備は, 保温性においてJARE装備よりすぐれている結果が得られた。また, 運動能力テストの8項目においては, 「立ち幅跳び」でスポーツウエアがJAREおよびエスキモー装備よりすぐれた成績であったが, 他の項目では, 「伏臥上体反らし」でエスキモーの装備がやや低い成績のほかは, ほぼ同様の値であった。JARE装備は, 身体的作業を行うのに適していると考えられる。ただし, JAREの作業手袋は保温性が著しく低く, 検討を要する。 The heat insulation and the physical performance were tested to compare the winter clothing of the JARE with that of Greenland Eskimos. Four healthy students were chosen as subjects. In the heat insulation test, each subject's body temperature was monitored during 60 min in chamber (-40℃). The condition of bicycle ergometer exercise was 2.5 kp×15 min. The results revealed the following : In heat insulation the Eskimo outfit excels the JARE outfit. In the physical performance test, the sportswear proves better in "broad jump" than the JARE and Esikimo outfit. But in the seven other items of the test, the three kinds of clothing showed almost the same result, though the Eskimo outfit was a little lower in "trunk flexibility". The JARE outfit seems suitable for physical activity, but its gloves require some improvements in heat insulation so as to cope with the severe cold. departmental bulletin paper